Development of Wordwall-based Indonesian Geographical Condition Assessment Instrument in Modipaskogo E-Book for Elementary School Students - Setiawati*, Ika; Wardani, Sri; Lestari, Wahyu (Universitas Syiah Kuala, 2024)
The ability to develop assessment instruments is an integral part of pedagogical skills that are needed by teachers to achieve optimal learning outcomes, the reality in the field is that the implementation of learning evaluation is still conventional with paper and pencil test instruments, has not utilized technology, especially in science learning Indonesian Geographical Conditions material in class V, lack of understanding or teacher trust in the use of alternative instruments that in accordance with the learning model developed, so that the learning outcome data obtained by class V students is not so optimal. As many as 65% of the number of students have not been able to achieve learning goals, besides that students look less motivated and not excited when working on learning evaluations. The purpose of this study is to develop a Wordwall-based assessment instrument in the Modipaskogo E-Book (Geographical Conditions IPAS Module). The method used in this study is the research and Development (RD) Model ADDIE (analysis, design, development, implementation, and evaluation). Based on data analysis and discussion, the conclusions of the Wordwall-Based Indonesian Geographical Conditions assessment instrument in the Modipaskogo E-Book are valid, reliable, very effective, and very practical to use.